Circulating miRNAs in maternal plasma as potential biomarkers of early pregnancy in sheep - Hitit, Mustafa; Kose, Mehmet; Kaya, Mehmet Salih; Kırbas, Mesut; Dursun, Sukru; Alak, Ilyas; Atli, Mehmet Osman (Frontiers in Genetics, 2022)
The aim was to assess plasma miRNA profiles during the peri-implantation and ascertain potential candidate miRNA markers for early pregnancy diagnosis in ovine plasma. The plasma samples were obtained from a total of 24 ewes on days 12 (pre-implantation; P12, n = 4), 16 (implantation; P16, n = 4) and 22 (post-implantation; P22, n = 4) after mating, and on their corresponding days of 12 (Pre-C; C12, n = 4), 16 (Imp-C; C16, n = 4) and 22 (Post-C; C22, n = 4) of the estrous cycle. The miRNA profiles in plasma were assessed by microarray technology. We detected the presence of 60 ovine-specific miRNAs in plasma samples. Of these miRNAs, 22 demonstrated a differential expression pattern, especially between the estrous cycle and early pregnancy, and targeted 521 genes. Two miRNAs (oar-miR-218a and oar-miR-1185-3p) were confirmed using RT-qPCR in the ovine in plasma samples. Protein-protein interaction (PPI) network of target genes established six functional modules, of which modules 1 and 3 were enriched in the common GO terms, such as inflammatory response, defense response, and regulation of immune response. In contrast, module 2 was enriched in the developmental process involved in reproduction, embryo development, embryonic morphogenesis, and regulation of the developmental process. The results indicate that miRNAs profiles of plasma seemed to be modulated during the peri-implantation stage of pregnancy in ewes. Those miRNAs may be used to advance a promising candidate for diagnosis in early ovine pregnancy.